Study of tobacco and alcohol consumption among students of a medical college in a city of Maharashtra - Gaikwad, Arvind V.; Priya, Rashmi; Dhande, Vishal S.; Doibale, Mohan K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Over the years, substance use has increased drastically in every section of the society. Tobacco and alcohol consumption in medical fraternity is quite common. The objectives of the study were to find out the prevalence of tobacco and alcohol consumption in medical students and to find out various reasons to start these habits. Methods: It was a cross-sectional study conducted in Government Medical College, Aurangabad during September to November 2018. Study was conducted amongst undergraduate MBBS students. Taking prevalence as 47%, allowable error 10% and 10% non-respondents the sample size comes as 85. By lottery method, third year medical students were selected randomly for the study. Completed data from 120 students were included in the study. Pre-designed semi-structured self-administered questionnaire was used for data collection. Trial version of SPSS software was used for statistical analysis. Results: In the present study, overall prevalence of substance use among undergraduate MBBS students was found to be 52.5% out of which 61.6% were males and 29.4% were females. Peer pressure was the main reason of continuing the habit (93.2%). 66% of these substance users showed willingness to quit the habit. Conclusions: High prevalence of tobacco and alcohol consumption was observed among undergraduate medical students.